Demonstrasi Gasifikasi Tempurung Kelapa pada Masyarakat Desa - Vidian, Fajri; Fitriani, Heni; Arief, Taufik; Alian, Helmy; Yani, Irsyadi; Hadi, Qomarul; Thamrin, Ismail; Zulkarnain, Zulkarnain; Manik, Dion Daud; Rasyid, Abdul; Simarmata, Johanes; Situmeang, Abetnego; Paroluan, Brian Einstein; Doloksaribu, Mikael (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The dedication to this activity was prompted by the lack of awareness about the potential use of coconut shells as gas fuel, like LPG, in Tebing Gerinting Selatan Village, as well as in Ogan Ilir Villages in general. The main aim of this activity is to educate the community in Tebing Gerinting Selatan on the technology of converting coconut shells into gas fuel using gasification technology. The educational process includes presentations, demonstrations, and discussions. During the demonstration phase, participants were shown how to operate coconut shell gasification equipment to produce gas fuel. The results of this activity were very encouraging as many participants showed a keen interest in the process and equipment used during the discussion phase. Based on the success of this activity, it can be concluded that there is a high level of public interest in coconut shell gasification technology, and there is a strong desire to apply this equipment to the kerupuk kemplang grilling process in the village.